THE IMPACTS OF CASH WAQF LINKED SUKUK EMPOWERMENT PROGRAMS: EMPIRICAL EVIDENCE FROM INDONESIA - Yumna, Aimatul; Masrifah, Atika Rukminastiti; Muljawan, Dadang; Noor, Feri; Marta, Joan (Journal of Islamic Monetary Economics and Finance, 2024)
This study analyzes the impact of Cash Waqf Linked Sukuk (CWLS) empowerment programs on beneficiaries’ welfare, financial inclusion, social participation, and spirituality. Using questionnaires administered to the beneficiaries and non-beneficiaries of the empowerment programs in Central Lampung, South Tangerang, Trenggalek East Java, and Bima Nusa Tenggara Indonesia, the study constructs three impact indicators: the welfare index, financial inclusion index, and social and spiritual index. The data are analyzed using the difference-in-difference (DiD) method, where the three impact indices are compared between the two groups of respondents in 2021 and 2022. We find that the CWLS empowerment programs improve the welfare and financial inclusion of beneficiaries but have no discernible effect on social and spiritual participation. However, the DID analysis reveals that the overall impacts of welfare, financial inclusion, and social and spiritual participation are not statistically different between beneficiaries and non-beneficiaries in 2021 and 2022. This study provides significant implications for policymakers and nadzir to enhance the impacts of CWLS on socioeconomic development and poverty alleviation. Acknowledgment This research was funded by Departemen Ekonomi dan Keuangan Syariah (DEKS), Bank Indonesia.